1998
DOI: 10.1086/514991
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Prosthetic Joint Infection: Case‐Control Study

Abstract: We conducted a matched case-control study to determine risk factors for the development of prosthetic joint infection. Cases were patients with prosthetic hip or knee joint infection. Controls were patients who underwent total hip or knee arthroplasty and did not develop prosthetic joint infection. A multiple logistic regression model indicated that risk factors for prosthetic joint infection were the development of a surgical site infection not involving the prosthesis (odds ratio [OR], 35.9; 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
488
7
58

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(569 citation statements)
references
References 44 publications
16
488
7
58
Order By: Relevance
“…We did not confirm the findings of some study groups who reported an increased risk of deep infection in RA patients both in TKR and THR (13,16). Nor did we agree with Berbari et al (12), who reported no increased risk in TKR as well as THR (Table 3). …”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We did not confirm the findings of some study groups who reported an increased risk of deep infection in RA patients both in TKR and THR (13,16). Nor did we agree with Berbari et al (12), who reported no increased risk in TKR as well as THR (Table 3). …”
Section: Discussioncontrasting
confidence: 89%
“…There are conflicting reports on whether this increased baseline risk of infections in RA patients might influence the risk of deep infection after primary total joint replacement surgery (1,5,(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg. Although no patients in our study developed deep infection, which prevents us from evaluating the association of poor glycemic control with deep infection, previous studies reported that patients who develop superficial surgical site infection are at greater risk for deep periprosthetic joint infection [3,24,26].…”
Section: Discussionmentioning
confidence: 62%
“…Some authors have suggested different adjunctive criteria [5,27,36,38] to overcome shortcomings of bacteriologic culture, leading to discrepancy in their inclusion and exclusion criteria. To resolve this inconsistency, an expert panel from the Musculoskeletal Infection Society (MSIS) has reviewed existing evidence and published a set of diagnostic criteria for PJI [30].…”
Section: Introductionmentioning
confidence: 99%